Evaluation of an Academic Satisfaction Model for First-year University Students - Zalazar Jaime, Mauricio Federico (2017)
In Argentina, when enrolling in higher education students are confronted with a series of challenges that can affect both their academic performance and psychological wellbeing. In addition to this, it has been shown that the highest academic dropout rate in Argentine public universities occurs during the first year of study. Therefore, the objective of this study was to evaluate the Academic Satisfaction model in a first-year university student population in Argentina, since said construct has proven to be a key contribution with regards to academic behavior (Özgüngör, 2010). 682 first-year university students participated in this study, mainly women (55.1%) and first-year students under the age of 20 (M=20.91; SD=5.39). The results supported what the original Academic Satisfaction model (Lent, 2004) proposed, demonstrating significant contributions on all paths. However, the relationship between perceived support for goal progress and outcome expectations were not replicated. In general terms, the model presented an optimal fit, showing that the proposed model adequately explains the process for forming opinions about Academic Satisfaction in the first-year university student population in Argentina.